Fructose promotes ampicillin killing of antibiotic-resistant Streptococcus agalactiae - Xuan-Wei Chen; Jia-Han Wu; Ying-Li Liu; Hetron Mweemba Munang’andu; Bo Peng (Virulence)
Streptococcus agalactiae (GBS) is an important pathogenic bacteria that infected both aquatic animals and human beings, causing huge economic loss. The increasing cases of antibiotic-resistant GBS impose challenges to treat such infection by antibiotics. Thus, it is highly demanded for the approach to tackle antibiotic resistance in GBS. In this study, we adopt a metabolomic approach to identify the metabolic signature of ampicillin-resistant GBS (AR-GBS) that ampicillin is the routine choice to treat infection by GBS. We find glycolysis is significantly repressed in AR-GBS, and fructose is the crucial biomarker. Exogenous fructose not only reverses ampicillin resistance in AR-GBS but also in clinic isolates including methicillin-resistant Staphylococcus aureus (MRSA) and NDM-1 expressing Escherichia coli. The synergistic effect is confirmed in a zebrafish infection model. Furthermore, we demonstrate that the potentiation by fructose is dependent on glycolysis that enhances ampicillin uptake and the expression of penicillin-binding proteins, the ampicillin target. Our study demonstrates a novel approach to combat antibiotic resistance in GBS.